A case of granulomatosis with polyangiitis-associated scleritis presenting as conjunctivitis - Aashna Doshi; Mauli Shah; Bhaskar Srinivasan; Parthopratim Dutta Majumder (Oman Journal of Ophthalmology, 2024)
A 42-year-old male presented initially with conjunctivitis and was treated with topical medical medications without any improvement. He developed ocular pain subsequently and further examination revealed lid edema, conjunctival hyperemia with chemosis, matting of lashes with yellowish discharge, and deeper episcleral congestion which did not blanch with topical vasoconstrictor. Subsequent laboratory investigation revealed positive cytoplasmic-antineutrophil cytoplasmic antibody (Anti-PR 3 antibody). He continued to develop recurrences and finally responded to oral azathioprine. Granulomatosis with polyangitis may rarely present as conjunctivitis and subsequently manifest as scleritis.